How the Nitrogen Economy of a Perennial Cereal-Legume Intercrop Affects Productivity: Can Synchrony Be Achieved? - Crews, Timothy E.; Kemp, Laura; Bowden, James H.; Murrell, Ebony G. (Frontiers in Sustainable Food Systems, 2022)
The UN’s Sustainable Development goal of Zero Hunger encompasses a wholistic set of targets that range from ending hunger by 2030, to addressing the socio-economic structures and food system vulnerabilities that contribute to food insecurity in the first place. Securing and managing soil nutrients remains one of the most basic challenges to feeding a growing number of people. This challenge is especially difficult because not only is it necessary to improve accessibility to nutrients for many of the world’s farmers, but it is also essential to simultaneously reduce the cycling of reactive nutrients in order to re-establish the planet within critical planetary boundaries. In recent years, progress has been made in developing perennial grain crops that show promise to dramatically improve on a range of ecosystem functions that tend to be well-developed in natural ecosystems but become compromised following land conversion to row crop agriculture. Recently work has begun to explore the competitive and facilitation dynamics of perennial legume-cereal intercrops. Here we report on a multi-faceted, five-year experiment in which intermediate wheatgrass (IWG) (Thinopyrum intermedium), a perennial relative of wheat that is bred to produce the grain Kernza®, was intercropped in alternating rows with the perennial legume alfalfa (Medicago sativa). The performance of the unfertilized intercrop was compared with monocropped IWG treatments, with and without urea-N applications, planted at two row densities such that the intercrop could be interpreted as either an addition or substitution design. We report measurements of aboveground net primary productivity of IWG and alfalfa, IWG grain yield, total N removed at harvest, ecosystem N balance, net N mineralization, leaf chlorophyl density (SPAD), root biomass and nitrous oxide emissions from all or a subset of treatments. Biomass and grain yields in the IWG-alfalfa intercrop were the most consistent of any treatment for the duration of the experiment. The intercrop had significantly lower nitrous oxide emissions compared to monocropped IWG plots that received urea. While intercrop compatibility of these two species appears high, there were signs of N limitation early in the experiment. We suggest innovations that may help to alleviate early N limitation in this novel agroecosystem.